The Soviet occupation of Germany : hunger, mass violence, and the struggle for peace, 1945 - 1947 - Slaveski, Filip (Cambridge University Press, 2013)
This is a new account of the Soviet occupation of postwar Germany and the beginning of the Cold War. Dr Slaveski shows how in the immediate aftermath of war the Red Army command struggled to contain the violence of soldiers against German civilians and, at the same time, feed and rebuild the country